أسلوب العتاب والعقاب في السنة النبوية = The modes of admonition and punishment in Prophet’s teachings = Kaedah teguran dan hukuman menerusi ajaran Rasulullah SAW - Salim, Ibrahim Muhammad Ali; Mohammed Yaqub, Mohammed Abullais Shamsuddin (IIUM Press, International Islamic University Malaysia, 2018)
يخطئ بعض المعلمين في معالجة أخطاء الطلبة، أو تقويم سلوكهم الـمَشِين، فيتبع أساليب غير تربوية، كأن يعتدي على الطالب بالضرب المبرح، أو يُعرِّضه للإهانة بين زملائه، مما يُسبِّب أضرارًا نفسيةً واجتماعيةً لدى الطلاب، ويزرع فيهم الخوف والهلع، مع أن الواجب على المعلم أن يُغلِّب الحكمةَ والمصلحةَ، ويبتعد عن الغلظة والقسوة، وجاء هذا البحث ليظهر هدي النبي في معالجة الأخطاء، وأسلوبه في معاتبة أو معاقبة الصحابة. والمنهجُ المتّبَعُ للبحث هو المنهج الاستقرائي، المتمثل في استقراء وتتبع أحاديث صحيح البخاري وصحيح مسلم لاستخراج الأحاديث التي لها علاقة بالموضوع، والمنهج التحليلي لاستنباط أساليب العتاب والعقاب في منهج النبي، وتحليل النصوص وشرحها. وقد انتهى البحث إلى عدة نتائج، منها: أن النبي استعمل أساليب لتقويم السلوك، ومنها: أسلوب العتاب والتأنيب فيغلظ القول على المخطئ، وكان من عادته في التأنيب التلميح بالخطأ دون التصريح بفاعله. وإنَّ أسلوب العقاب في السنة كان على نوعين: الأول: العقاب النفسي كالهجر، والحرمان من الحقوق، والدعاء على المخالف المتكبر، والنوع الثاني: العقاب البدني، وهو الإيذاء اليسير الذي لا يصل إلى رتبة الضرب كالوخز والدفع. وبيَّن البحث أقوال الفقهاء في حكم استعمال الضرب كوسيلة لمعاقبة الطلاب، وذكر الضوابط الشرعية لها. ********************************************************* Some teachers err in dealing with the mistakes of their students and evaluation of their misbehaviors. They follow non-educational methods such as assaulting the student with severe beatings or insulting him in front of his colleagues, causing psychological and social demoralization of the students. They were supposed to deal with wisdom and public interest (maÎlaÍah) in this matter, rather than becoming dominant by the flow of arrogance and cruelty. This research aims to show the guidance of the Prophet Muhammad (peace be upon him) in dealing with faults, and his style of addressing such issues while educating his companions. The method employed in this research is the inductive, whereby hadith of SahÊÍ al-BukhÉrÊ and SaÍÊÍ Muslim related to the subjects are extracted and extrapolated. In Addition, the analytical method is used to devise means and approaches, analyze the texts, and explain them. The research ended with findings such as the Prophet used several methods to evaluate the behavior, including the method of admonition and reprimanding and at times he scolded harshly when necessary. It was also a habit of Prophet Muhammad (peace be upon him) that he used to rebuke pointing on the mistakes without referring directly to the person. ********************************************************* Sesetengah guru tersasar dalam menangani kesilapan dan menilai tingkah laku tidak baik yang dipamerkan oleh para pelajar. Mereka menggunakan kaedah-keadah yang tidak bersifat mendidik seperti mencederakan mereka dengan pukulan dan mencela mereka di hadapan teman-teman yang kesannya membawa kepada tekanan psikologi dan sosial pada diri pelajar. Para guru sepatutnya menangani masalah ni dengan penuh hikmah dan perlu melihat kepada maslahah para pelajar bukannya menggunakan kekerasan dan kezaliman. Kajian ini menunjukkan beberapa panduan Rasulullah dalam menghadapi kesilapan atau kesalahan para sahabat, dan cara baginda menanganinya yang bersifat mendidik. Kajian ini menggunakan kaedah induktif dimana hadis-hadis daripada Sahih al-Bukhari dan Muslim yang berkaitan dengan isu ini di petik dan diekstrapolasi. Selain itu kajian ini menggunakan kaedah analitikal untuk menganalisa teks dan membuat penerangan. Kajian ini mendapati bahawa Rasulullah saw menggunakan beberapa kaedah untuk menilai tingkah laku termasuklah kaedah memberi nasihat dan teguran dan kadangkala baginda menggunakan kata-kata tegas mengikut kesesuaian keadaan. Ia juga merupakan cara Rasullullah saw apabila merujuk kepada kesalahan tertentu tanpa menuding jari pada si pelaku.